2005
DOI: 10.1128/jcm.43.7.3140-3144.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relatedness between Pneumococcal Populations Originating from the Nasopharynx, Adenoid, and Tympanic Cavity of Children with Otitis Media

Abstract: Previous studies have shown that Streptococcus pneumoniae exists in both middle ear effusions and the upper respiratory region from children with otitis media with effusion (OME), but it remains unclear whether these strains represent genetically identical clones. Therefore, it cannot be determined whether these bacteria originate from a common source. To determine the presence of pneumococci at different anatomical locations of OME patients, conventional culture and PCR techniques were used. To analyze the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Additionally, surveillance for changes in the epidemiology of invasive serotypes of pneumococci is crucial to preserving the reductions in the frequency of bacteremia, pneumonia, and otitis media that have followed the introduction of pneumococcal vaccines. Such surveillance is especially important given the reality of capsular switching and the emergence of antimicrobial resistance even in genetically related strains of pneumococci (5,12). We conclude that strains of pneumococci recovered from the blood and respiratory tracts of patients with pneumonia usually (about 90% of the time) have the same PFGE and susceptibility patterns as well as the same serotypes.…”
mentioning
confidence: 77%
“…Additionally, surveillance for changes in the epidemiology of invasive serotypes of pneumococci is crucial to preserving the reductions in the frequency of bacteremia, pneumonia, and otitis media that have followed the introduction of pneumococcal vaccines. Such surveillance is especially important given the reality of capsular switching and the emergence of antimicrobial resistance even in genetically related strains of pneumococci (5,12). We conclude that strains of pneumococci recovered from the blood and respiratory tracts of patients with pneumonia usually (about 90% of the time) have the same PFGE and susceptibility patterns as well as the same serotypes.…”
mentioning
confidence: 77%
“…Colonisation of the nasopharynx is the source of bacteria that cause AOM (Hotomi et al 2004, Tonnaer et al 2005, and therefore the initiating site for almost all OM phenotypes. Colonisation occurs rapidly after birth, and the nasopharyngeal bacterial flora is established in the first year of life (Garcia-Rodriguez & Fresnadillo Martinez 2002).…”
Section: Evolution Of Nasopharyngeal Bacteriamentioning
confidence: 99%
“…Research has shown a genetic relatedness between pneumococcal populations sampled from middle ear fluid, oropharyngeal swab, and adenoidal biopsy in 80% of children undergoing tube insertion for OME and 90% of children with recurrent acute otitis media [37]. This suggests that pneumococci in middle ear effusions are likely to originate in the nasopharynx, and it proposes a role for the adenoid biofilm in propagating recurrent bouts of acute otitis media and OME.…”
Section: Otitis Mediamentioning
confidence: 99%